Study of Local Wisdom Nyadran Sruwen Hamlet as Ethnoscience and Environmental Ethics - Amidi Amidi; Andin Vita Amalia; Budi Prasetyo; Fitri Daeni; Imamuddin Zaid Rahmatillah; Muhammad Anwar Fadholi (Unnes Science Education Journal, 2023)
Tradition is a custom that is carried out from generation to generation from ancestors. One of the traditions that until now maintained by the people of Java is the tradition of Nyadran. The Nyadran tradition carried out by most Javanese people has become an important part of life for the Javanese people as well as for the people in Sruwen Hamlet, Semarang Regency. This study aims to examine the viewpoint of Nyadran tradition that exists in the people of Sruwen Hamlet, Semarang Regency based on ethnoscience and the relationship of Nyadran tradition with environmental ethics. This study was designed in the form of descriptive-qualitative research. Data collection techniques used are observation techniques, interview techniques, and documentation techniques. The results of the study in the form of data interviews with three speakers in the hamlet Sruwen. Instruments. the questions presented consisted of nine questions that explore information related to the implementation of Nyadran and Nyadran’s relationship with protecting the environment. Based on research that has been done, it can be concluded that Nyadran tradition can be used as a medium of ethnoscience-based learning in science learning and there is a relationship between Nyadran tradition and environmental ethics.